A novel pillar[5]arene-based chemosensor for dual-channel detecting L-Arg by multiple supramolecular interactions. (December 2019) - Chen, Yan-Yan; Gong, Guan-Fei; Zhang, You-Ming; Fan, Yan-Qing; Guan, Xiao-Wen; Zhou, Qi; Yang, Hai-Long; Yao, Hong; Wei, Tai-Bao; Lin, Qi
Abstract: As one of the vital amino acids in human body, l -Arginine (L-Arg) plays important roles in many biological functions, and the development of convenient detection L-Arg is essential in the current research. Herein, a novel pillar[5]arene-based fluorometric and colorimetric dual-channel sensor (PNS ) was designed and synthesized, which exhibited superior performance for detecting L-Arg. The colorimetric and fluorometric limits of detection (LODs) for L-Arg are 0.6 μM and 0.2 μM, respectively. In addition, the sensing process ofPNS for L-Arg showed excellent selectivity and the sensing mechanism was based on multiple surpramolecular interactions. Meanwhile, PNS -based test paper has been prepared, which could act as a convenient and efficient test kit to detect L-Arg in water. Graphical abstract: Herein, a novel pillar[5]arene-based fluorometric and colorimetric dual-channel sensor (PNS ) was designed and synthesized, which exhibited superior performance for detecting L-Arg. The colorimetric and fluorometric limit of detections ofPNS (LODs) for L-Arg are 0.6 μM and 0.2 μM, respectively. In addition, the sensing process ofPNS for L-Arg showed excellent selectivity and the sensing mechanism was based on multiple surpramolecular interactions. Meanwhile, PNS -based test paper has been prepared, which could act as a convenient and efficient test kit to detect L-Arg in water.Image 1 Highlights: Novel pillar[5]arene-based fluorometric and colorimetric L-Arg sensor. Sensing L-Arg by multiple supramolecular interactions. Selectively and sensitively detection L-Arg. The LODs for dual-channel detecting L-Arg could reach to 0.2 μM. ThePNS -based test paper for detecting L-Arg in water was prepared.